Portrait of High School and Islamic Boarding School Students’ Understanding in Yogyakarta Special Region and Central Java Regarding Non-Halal Food Ingredients: Potret pemahaman siswa SMA beberapa sekolah dan pesantren di DIY dan Jawa Tengah tentang bahan makanan non-halal - Muhammad iqbal; Ahmad Nurrozi (Yayasan Nurul Musthafa, 2026)
This study aims to analyze the basic understanding of senior high school students and Islamic boarding school (pesantren) students who constitute the target market of the Islamic Economics Study Program at Universitas Islam Indonesia regarding non-halal food ingredients. The study employed a mixed-method approach, providing an overview of differences in understanding through both quantitative and qualitative analyses. A survey was conducted involving 332 respondents, consisting of male and female students from various schools and pesantren in the Special Region of Yogyakarta and Central Java. Quantitative analysis was carried out descriptively to identify differences in understanding based on gender and school background. Meanwhile, qualitative analysis explored the underlying factors contributing to differences in responses. The results indicate that the majority of pesantren students do not yet have a comprehensive understanding of halal law and its practical implementation. Differences in understanding were also clearly observed between male and female students, as well as among schools. Therefore, a specifically designed educational program is needed to enhance their understanding and to further strengthen awareness of halal issues. [Penelitian ini bertujuan untuk menganalisis pemahaman sederhana siswa SMA dan santri pesantren yang menjadi target pasar program studi ekonomi Islam Universitas Islam Indonesia terkait pemahaman mereka akan bahan makanan non-halal. Metode yang digunakan adalah mixed method, yang memberikan gambaran tentang perbedaan pemahaman melalui analisis kuantitatif dan kualitatif. Survei dilakukan pada 332 responden, yang terdiri dari siswa putra dan putri di berbagai sekolah dan pesantren di DIY, Jawa Tengah. Analisis kuantitatif dilakukan secara deskriptif untuk mengidentifikasi perbedaan pemahaman berdasarkan jenis kelamin dan sekolah. Sementara itu, analisis kualitatif mendalami faktor-faktor yang melatarbelakangi perbedaan jawaban. Hasil menunjukkan bahwa mayoritas santri belum memahami secara mendalam hukum halal dan cara penerapannya. Perbedaan pemahaman juga terlihat jelas antara putra dan putri, serta antar sekolah. Oleh karena itu, diperlukan program edukasi khusus yang dirancang untuk meningkatkan pemahaman mereka, sehingga kesadaran akan halal dapat terus meningkat.]